Juvenile-Onset Recurrent Respiratory Papillomatosis Aggressiveness: In Situ Study of the Level of Transcription of HPV E6 and E7 - Charles Lépine (Cancers, 2020)
Juvenile-onset recurrent respiratory papillomatosis (JoRRP) is a condition related to HPV 6 and 11 infection which is characterized by the repeated growth of benign exophytic papilloma in the respiratory tract. Disease progression is unpredictable: some children experience minor symptoms, while others require multiple interventions due to florid growth. The aim of this study was to explore the biomarkers of JoRRP severity on a bicentric cohort of forty-eight children. We performed a CISH on the most recent sample of papilloma with a probe targeting the mRNA of the E6 and E7 genes of HPV 6 and 11 and an immunostaining with p16INK4a antibody. For each patient HPV RNA CISH staining was assessed semi-quantitatively to define two scores: 1+, defined as a low staining extent, and 2+, defined as a high staining extent. This series contained 19 patients with a score of 1+ and 29 with a score of 2+. Patients with a score of 2+ had a median of surgical excision (SE) per year that was twice that of patients with a score of 1+ (respectively 6.1 versus 2.8, p = 0.036). We found similar results with the median number of SE the first year. Regarding p16INK4a, all patients were negative. To conclude, HPV RNA CISH might be a biomarker which is predictive of disease aggressiveness in JoRRP, and might help in patient care management.